The influence of style and origin on mineral composition of beers retailing in the UK - Rodrigo, S.; Young, Scott D.; Talaverano, M.I.; Broadley, Martin R. (Springer, 2016)
Beer has high nutritional values in terms of energy and is also a dietary source of antioxidants, carbohydrates and minerals among others. In Europe, 53 Mt of beer are produced annually, and with an average supply of 68.2 kg capita‾¹ year‾¹ among adults. In this study, the mineral composition of 125 commercial beer samples retailing in the UK, but originating from ten countries, was determined; such detailed information is lacking in UK food composition tables. Beer composition data are reported for Al, As, Ba, Ca, Cd, Co, Cr, Cs, Cu, Fe, K, Mg, Mn, Mo, Na, Ni, Pb, Se, Sr, U, V and Zn, following analysis by inductively coupled plasma mass spectrometry. ANOVA results showed higher concentrations of Mo, Pb and Sr (0.160; 491.70 × 10‾⁵; 0.38 mg L‾¹, respectively) for stout/porter style and a significant higher amount of minerals such as Al (3.835 mg L−1), Cd (8.64 × 10−5 mg L‾¹), Mn (1.02 mg L‾¹) or Ni (0.312 mg L‾¹) among others for lambic beer. Regarding the country of origin, higher Se concentrations were reported from beer brewed in the USA (0.110 mg L‾¹). It is concluded that beer style was determined to have a greater effect on beer mineral composition than origin or container type.